MODAL MANUSIA DAN PERTUMBUHAN EKONOMI DI INDONESIA MENGGUNAKAN ESTIMASI PANEL - Indra Suhendra (Jurnal Ekonomi-Qu, 2020)
This study examines the influence of the human capital (HC) variable on economic growth (EG) in Indonesia. The study used a panel data model with fixed effect estimates for 34 provinces from 2011 to 2019. We used the education index formula from the United Nations Development Program (UNDP) to estimate human capital. The results showed that the human capital variable in the current year (HC) to human capital year-3 (HCt-3) had a negative and significant effect on economic growth. Meanwhile, variable of the human capital year-5 (HCt-5) to human capital year-7 (HCt-7), has a significant positive effect on economic growth. This study also found that the human capital variable year-4 (HCt-4), although the direction is positive, is not statistically significant for economic growth. This paper is useful for policy makers in Indonesia to increase human capital by improving the quality of education.